Letters from Salonika, 1908 - Dimitrijević, Jelena J., 1862-1945. (Piscataway, NJ)
xi, 182 sayfa
Keywords: “An English translation of the Letters from Salonika by Jelena Dimitrijević, accompanied by a substantial critical introduction and a commentary. The book comprises author’s impressions from Salonika in the summer of 1908, in the midst of the Young Turk Revolution. The narrative focuses on the question of the “unveiling” of Muslim women, but also vividly portrays the vanished cityscape of Ottoman Salonika and gives accounts of the city’s Turkish, Jewish, Mu’min, and Greek communities“ -- Yayıncı.